Nisbah Antara Ilmu Pengetahuan, Filsafat, dan Agama - Yasmin, Nur Asyiffa Amalia; Nursandi, Nuri (Madani: Jurnal Ilmiah Multidisiplin, 2024)
Science functions to search for scientific truth. In the Islamic view, knowledge is considered important for humans to achieve worldly prosperity and deepen their knowledge of God. This article aims to examine the definition of science, its characteristics, as well as the similarities and differences between science, religion and philosophy. Science, religion and philosophy are three elements that can guide humans in their search for truth, but they have significant differences. This article uses the Library research discussion method. This method relies on scientific works that have been published by researchers as the main data source. In this context, research is called "Library Research" because the materials and data required for research come from library collections, such as books, encyclopedias, documents and other periodic publications. The results of the study show that Islam, as a religion that respects the role of reason, certainly really appreciates the existence of philosophy. This is because philosophy, which uses reason as a means to achieve truth, has fundamental similarities with Islam which values the use of reason. Science is a conscious effort to investigate and understand various aspects of reality in human nature, as well as to improve human understanding. However, these aspects are only limited to open formulations. Science creates certainty by limiting its scope, and the certainty of knowledge arises from its limitations. Science is not just a collection of information, but is a summary of knowledge that is based on approved theories and can be tested systematically through various techniques used in a particular field. In general, the goal of science is to discover scientific facts using scientific principles.